Economic Integration versus Social Avoidance: Assessing Neighborhood Relationships Between the Shanty Town of Calabar and its Surrounding Upper-class Gated Communities | Integração econômica vs evitamento social: analisando relações de bairro entre a favela de Calabar e os condomínios de elite circundantes - Treuke, Stephan (Revista Brasileira de Estudos Urbanos e Regionais, 2019)
This research assesses the impact of neighborhood effects on the well-being of thirty inhabitants in Calabar, a shanty-town set within an upper-class area of Salvador (Brazil). We adopted a threefold methodological framework in order to explore the material, social and symbolic dimensions of the neighborhood effects based on a set of interviews. With regard to the material dimension, cross-class interactions via the employment nexus are fostered through geographic proximity; however social segmentation regarding access to schools, hospitals and leisure activities have reinforced the social hierarchies. In the social dimension, a high degree of cohesion and solidarity has entailed positive implications for the job search processes, access to resources and a strengthening of territorial identity. With the symbolic dimension, statistical discrimination has entailed deleterious effects on economic integration. In conclusion, the hypothesis of an opportunity-enriching environment should be subjected to careful scrutiny since the economic integration of the inhabitants neither bridges the social distances nor impedes place-based discrimination.